2016
DOI: 10.1002/2016gl068550
|View full text |Cite
|
Sign up to set email alerts
|

Influences and interactions of inundation, peat, and snow on active layer thickness

Abstract: Active layer thickness (ALT), the uppermost layer of soil that thaws on an annual basis, is a direct control on the amount of organic carbon potentially available for decomposition and release to the atmosphere as carbon‐rich Arctic permafrost soils thaw in a warming climate. We investigate how key site characteristics affect ALT using an integrated surface/subsurface permafrost thermal hydrology model. ALT is most sensitive to organic layer thickness followed by snow depth but is relatively insensitive to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 65 publications
3
43
0
Order By: Relevance
“…These two differences may explain why e.g. Atchley et al (2016) find a relatively small influence of water content on the insulating effect at the surface, since their model approach includes an organic layer. Although the focus of our study is on soil temperature, the process-based bryophyte and lichen scheme in JSBACH also provides an estimate of the organisms' net primary productivity (NPP).…”
Section: Discussionmentioning
confidence: 99%
“…These two differences may explain why e.g. Atchley et al (2016) find a relatively small influence of water content on the insulating effect at the surface, since their model approach includes an organic layer. Although the focus of our study is on soil temperature, the process-based bryophyte and lichen scheme in JSBACH also provides an estimate of the organisms' net primary productivity (NPP).…”
Section: Discussionmentioning
confidence: 99%
“…All analyses were conducted at the Daniel B. Stephens and Associates Laboratory. Measured thermal properties as a function of saturation were compared against common approximations for C and k typically used in thermal and cryohydrogeologic models (e.g., Atchley et al, ; Harp et al, ; Langer et al, ) in the absence of measured thermal properties: the volume fraction weighted approach for C from Hillel () and the Johansen () approach for k as presented in Peters‐Lidard et al (). Values for C for the constituents (i.e., air, water, and solid) are from Table 9.1 in Hillel (); organic matter was neglected.…”
Section: Methodsmentioning
confidence: 99%
“…This process of energy advection through taliks has been evaluated through numerical simulations (e.g., see review by Kurylyk et al, 2014). Some studies have used numerical models to project the development of taliks in terrestrial environments (Atchley et al, 2016;Engelhardt et al, 2010;Lawrence et al, 2012); however, few have documented and studied them in the field (Jin et al, 2006;Zenklusen Mutter & Phillips, 2012). The presence of relatively shallow taliks in terrestrial systems is rarely reported.…”
Section: /2017jf004469mentioning
confidence: 99%
“…Complete refreeze can generally be assumed in areas of continuous permafrost where low temperatures and abundant ground ice limit thaw (Woo & Young, ); however, talik conditions may also exist locally in colder climates where the ground thermal regime and high snow cover can restrict energy loss over winter. For example, using a permafrost thermal hydrology model and simulating future ALTs, Atchley et al (, Figure 4b) found that taliks may form at Barrow, Alaska, under inundated conditions with heavy snowfall.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation